Effects of Eccentric Cycling as Part of a Warm-Up Protocol on Various Athletic Performance Measures Among Recreationally Active Individuals - Liew, Yit (Auckland University of Technology, 2024)
The aim of the study was to investigate the effects of eccentric cycling as a part of the warm-up protocol on athletic performance in recreationally active individuals. Seventeen recreationally active individual participated in the study which involved two testing days. Each participant was randomly assigned to either a traditional warm-up (TWP) or a traditional warm-up plus eccentric cycling (TWPEC) on a custom-made machine on the first day. On the second testing day, participants crossed over to the alternative condition. The eccentric cycling protocol involved a 6-minute exercise targeting both the upper body (shoulder) and the lower body (glutes, hamstring). Each testing session began with a 5-minute jog followed by 10-minutes of joint mobility and dynamic stretches. Participants then followed their assigned protocol. The traditional warm-up group completed a standard warm-up routine followed by three 30-metre (m) sprints at 75%, 80%, and 85% of their maximal speed, with 30-seconds rests between each sprint. The eccentric group, after completing the traditional warm-up, performed an additional 6-minute eccentric cycling session (2 minutes each targeting the upper body, glutes, and hamstrings), followed by the same three 30m sprints at 75%, 80%, and 85% of their maximal sprint, with 30-second rests between each sprint. After a 4-minute rest, both groups completed five tests in the following order: a 30m sprint time, standing long jump distance, shoulder internal and external range of motion, 20-second hopping frequency, and the sit-and-reach flexibility test. Shoulder rotation was significantly greater (+3.0 degree, p = .005) following the TWPEC protocol. Statistical analyses were conducted using R, using linear mixed models to assess the effects of eccentric versus traditional warm-up on athletic performance metrics, including sprint times, jump distances, hopping frequency, and shoulder range of motion. ANOVA was performed on each model to report F-statistics, p-values, and partial omega squared (ω_p^2) for effect size estimation, with significance set at p < .05. The models accounted for individual participants as random effects and considered potential sequence effects in the analysis. Hopping frequency was significantly greater (+2.4 hops/second, p = .048) with the TWP protocol. No significant differences between the protocol for sprint times, jump performance and sit-and-reach flexibility. Additionally, there was a significant difference on the sequence, but no significant difference between the type of warm-up and the sequence in which they were performed. This suggests that the improvements in shoulder rotation were primarily due to the eccentric warm-up itself and not influenced by the order of the protocols. These results suggest that eccentric cycling could be beneficial to include as part of a warm-up for upper body activities that involve shoulder rotation while not necessarily providing significant advantages for lower body performance or overall flexibility. From a training or competition warm-up perspective, individuals who require overhead movement can consider using this method to improve subsequent performance and possibly reduce the risk of injury.